Has the FINRA Rule 2242 been successful in enhancing the quality of debt reports issued by sell-side analysts? - Charitou, Andreas; Karamanou, Irene; Petrou, Zacharias (My University, 2025)
The aim of this study is to examine the effect of the 2016 FINRA Rule 2242 on the reliability of debt analyst research reports. Through a comparative analysis of textual content before and after the rule's implementation, our results indicate a reduction in optimistic tone, and an increase in the language complexity and length of analyst reports in the post-rule period. Additional analysis shows reduced boilerplate language, greater specificity, and more quantifiable information, suggesting that the Rule enhanced the credibility of debt analyst research reports. We further corroborate these findings by providing evidence that in the post-rule period the relative informational efficiency of the debt market improves for firms covered by debt analyst research. We also find that following the implementation of the rule, the debt market reactions to positive and more complex reports are greater. We conclude that FINRA Rule 2242 was successful in curbing debt analysts’ conflicts of interest.
Keywords: Debt analysts; FINRA Rule 2242; Recommendations